Perspective effects during reading: evidence from text change-detection - Bohan, Jason; Filik, Ruth (Taylor and Francis, 2017)
We report two text change-detection studies in which we investigate the influence of reading perspective on text memory. In Experiment 1, participants read from the perspective of one of two characters in a series of short stories, and word changes were either semantically close or distant. Participants correctly reported more changes to perspective-relevant than -irrelevant words, and for distant than close changes. However, distance and perspective did not interact, suggesting that adopting a particular perspective did not lead to a more fine-grained analysis of perspective-relevant information. In Experiment 2, participants read one long narrative from the perspective of either a burglar or house-buyer. Results showed that only participants with a low working memory span showed perspective effects, suggesting that individual differences in working memory capacity appear to influence processing of perspective-relevant information.